National Science Education Standards : observe, interact, change, learn - National Research Council (U.S.) (Washington, DC : National Academy Press, 1996)
Includes chapters on Science Teaching Standards, Standards for Professional Development of Teachers, Assessment in Science Education and Science Education Program Standards
Overview -- Introduction -- Principles and definitions -- Science teaching standards -- Standards for professional development for teachers of science -- Assessment in science education -- Science content standards -- Science education program standards -- Science education system standards
"National Research Council"--Cover
Includes bibliographical references and index
530 Also available via the World Wide Web
Keywords: Science -- Study and teaching -- Standards -- United States; Exacte wetenschappen; Leerplanontwikkeling